Evaluation of Trabecular Bone Around the Impacted Maxillary Canine on CBCT Images by Fractal Analysis - Arslan, Zeynep Betül; Çelik, Berrin (UI Scholars Hub, 2023)
Objective: The aim of this study was to evaluate the position, angulation and surrounding trabecular bone structure of a unilateral impacted maxillary canine (IMC) tooth using fractal analysis. Methods: Cone beam computed tomography images of 50 patients (38 female, 12 male) with unilateral IMC were selected for this retrospective study. A 25x25 pixel region of interest (ROI) was selected in the trabecular bone between the premolars on the impacted and non-impacted side and fractal analysis was conducted. The angulation of unilateral impacted canines was measured and the position was categorized as vestibular, intra-alveolar and palatal. Results: Of the 50 impacted teeth, 42% were in the vestibular, 26% were in the intra-alveolar, and 32% were in the palatal position. The most common angulation angle of the IMC was 0°-15° which occurred in 44% of canines. While the bone fractal values did not statistically significantly differ between the sides, the values were 1.05 ± 0.9 on the impacted side and 1.04 ± 0.1 on the non-impacted side. No significant difference was observed in fractal values according to the position and angulation angles of the impacted maxillary canine (p > 0.05). Conclusion: The structure of trabeculation around the impacted canine tooth was no different than on the non-impacted side.